Analysis of Information Systems Capabilities and Performance of Firms in Telecommunications Industry, Kenya - Kipyegon, Bett, Alfred; Obura, Dr. Johnmark; Oginda, Dr. Moses (International Journal of Scientific Research and Management (IJSRM), 2018)
In the 21st century where economies are driven majorly by knowledge and information-based service businesses, telecommunication industries are playing a critical economic role both regionally and globally. In Kenya, with a combined subscription rate of 37.8 million based on a 2016/17 Communication Authority of Kenya report of 2017, Safaricom Kenya Limited controls about 71.2% of the subscribers, Airtel Kenya Limited is second with 17.6% with Telkom Kenya coming third with 7.4%. Finserve East Africa (Equitel) a new entrant in the market controls 3.8% of subscribers. These figures points to the fact that only Safaricom seems to be the only firm performing well. This reality forms the basis of establishing whether their difference in performance is attributable to their information systems capabilities. The purpose of this study was to analyse the relationship IS capabilities and performance of firms in the telecommunications industry in Kenya. It was anchored on Resource-Based Theory and guided by a conceptual framework with the dependent variable being firm performance while independent variable was IS capabilities. Correlational and survey research designs were used. The population of the study was 408 staff comprising all executive, management and operational level managers from the business and IT sections in each firm. A sample of 202 staff was drawn through proportionate stratified random sampling method. Primary data was collected using structured questionnaire and an interview schedule. Reliability of the research instrument was tested against Cronbach’s alpha coefficient where a reliability score of 0.814 was achieved while validity was gauged through research experts’ opinions. Data was analysed using both descriptive and inferential statistics. The findings established that IS capabilities and firm performance have a weak relationship (r = 0.409, p